OPTIMALISASI PERANAN PEMBINAAN MANAJEMEN KOPERASI DALAM MENINGKATKAN KINERJA KOPERASI DI KABUPATEN SUMEDANG - Ila Karmila; Dede Jajang Suyaman; Odang Kusmayadi (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The essence of the problem in this research is still not optimal implementation of cooperative management by cooperatives located in Sumedang District, many cooperatives who do not report to the Department of Cooperatives, small business, medium enterprises, trade and industry Sumedang. The purpose of this research is to know the role of coaching management cooperative by the Department of Cooperatives, Small business, intermediate, trade and industry Sumedang district. The method used in this research is a qualitative method of research by examining the three cooperatives that were used as samples in this study, namely the Indonesian Employee Cooperative Cooperative Health Officer Sumedang, employee cooperative PT. PLN (Persero) Sumedang, and BMT Al Amanah Sumedang. The result of this research is that the Department of Cooperative Department of Cooperatives, small business, medium enterprises, trade, Sumedang District has a strategic role in improving the quality of cooperatives in Sumedang district through the implementation of a better cooperative management system so that cooperatives in the cooperative performance in the district can be said quality, but still there are various barriers, namely the low cooperative resource , and the unavailability of information containers to accelerate the reporting and development of cooperative material management. Recommendation of the results of this research is necessary to the role of local governments in the increase in the development budget management cooperative, provision of adequate facilities and infrastructures, improvement of the quality of human resources cooperative cooperatives through education programs and level training, and improvement of the supervision of cooperatives by the Department of Cooperatives, small business, medium enterprises, trade industry Sumedang District.